Conventional versus modified delivery system technique in commissural alignment from the Evolut low‐risk CT substudy. Issue 3 (9th October 2021) - Tang, Gilbert H. L.; Sengupta, Aditya; Alexis, Sophia L.; Zaid, Syed; Leipsic, Jonathan A.; Blanke, Philipp; Grubb, Kendra J.; Gada, Hemal; Yakubov, Steven J.; Rogers, Toby; Lerakis, Stamatios; Khera, Sahil; et al.
Abstract: Objectives: We assessed the impact of conventional delivery system (DS) insertion technique on "Hat‐marker" orientation/commissural alignment in patients who underwent transcatheter aortic valve replacement (TAVR) in the Evolut Low Risk Trial CT substudy versus a modified technique. Background: Unlike surgical aortic valve replacement, where alignment of the surgical valve commissures with native commissures can be achieved virtually 100% of the time, commissural alignment during TAVR is not achieved consistently. This may subsequently impact the feasibility of both coronary access and reintervention after TAVR. Methods: "Hat‐marker" orientations during deployment were characterized as outer curve (OC), center front (CF), inner curve, and center back. Severe commissure‐to‐CA overlap was 0–20°. "Hat‐marker" orientations and CA overlap were compared to 240 patients from a single center using the modified 3‐o'clock flush port DS technique. Results: In the CT substudy in which conventional DS insertion was performed (flush port at 12 o'clock); 154/249 had both analyzable CT and procedural fluoroscopy to validate "Hat‐marker" to C‐tab/commissural orientation. On post‐TAVR CT, Evolut valve commissural orientation and coronary artery (CA) ostia were identified. Compared to conventional DS technique in the CT substudy, the modified technique had higher rates of "Hat‐marker" at OC/CF orientation, improved commissural alignment and reduced severe CA overlap; (left main, 14.2 vs. 27.9%; right coronary artery, 11.7 vs. 27.3% both, 5.0 vs. 13.6%; 1 or both CA, 20.8 vs. 41.6%, all p < 0.01). Conclusions: The modified technique improved initial "Hat‐marker" orientation during Evolut deployment and resulted in better commissural alignment and reduced CA overlap.